2015
DOI: 10.1016/j.epsl.2015.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Is the transition zone a deep reservoir for fluorine?

Abstract: International audienceIt is now recognized that the transition zone (TZ) is a significant repository for water. This means that other volatile species may also be stored in this region such as halogen elements. We have measured the solubility of fluorine in wadsleyite (Wd) and ringwoodite (Rw) under hydrous and anhydrous conditions at different pressures and temperatures, relevant for the transition zone. F contents are similar in Wd (665 to 1045 ppm F, up to 956 ppm H2O) and in Rw (186 to 1235 ppm F, up to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…We presented operando RBS and PIGE measurements applied to measure the lithium and the In summary, we have demonstrated how powerful ion beam techniques can be for investigating the lithium profile in lithium batteries. Interestingly, the distribution of others elements such as sodium or magnesium is also possible using the reaction 23 Na(p,p') 23 Na at 439 keV or 24 Mg(p,p') 24 Mg at 1368 keV [21,22] and is believed to be of great interest for studying reaction and degradation mechanisms in Na-ion and Mg-ion batteries.…”
Section: Resultsmentioning
confidence: 99%
“…We presented operando RBS and PIGE measurements applied to measure the lithium and the In summary, we have demonstrated how powerful ion beam techniques can be for investigating the lithium profile in lithium batteries. Interestingly, the distribution of others elements such as sodium or magnesium is also possible using the reaction 23 Na(p,p') 23 Na at 439 keV or 24 Mg(p,p') 24 Mg at 1368 keV [21,22] and is believed to be of great interest for studying reaction and degradation mechanisms in Na-ion and Mg-ion batteries.…”
Section: Resultsmentioning
confidence: 99%
“…In Roberge et al . (), coupled micro‐IBA methods (PIXE, PIGE, RBS, ERDA) were used to measure F and H in wadsleyite and ringwoodite under hydrous and anhydrous conditions relevant for the transition zone. Crystals of olivine, wadsleyite and ringwoodite could be clearly identified in the synthesised samples, and chemical heterogeneities such as NaF‐rich fine intergrowths in the grain boundaries could be detected.…”
Section: Advances In Accelerator‐based Methodsmentioning
confidence: 99%
“…Cr episson et al (2014) investigated fluorine incorporation in H-bearing forsterite, with high F solubilities (1715 and 1308 lg g -1 ) measured by PIGE in samples synthesised at 2 and 4 GPa, respectively, while ERDA was used to quantify H. The existence of clumped fluoride-hydroxyl defects in these nominally anhydrous minerals suggested that the F geodynamical and water cycles are strongly coupled. In Roberge et al (2015), coupled micro-IBA methods (PIXE, PIGE, RBS, ERDA) were used to measure F and H in wadsleyite and ringwoodite under hydrous and anhydrous conditions relevant for the transition zone. Crystals of olivine, wadsleyite and ringwoodite could be clearly identified in the synthesised samples, and chemical heterogeneities such as NaF-rich fine intergrowths in the grain boundaries could be detected.…”
Section: Examples Demonstrating the Capabilities Of Iba Techniques Inmentioning
confidence: 99%
“…Therefore, the potential of fluorine as an important charged species in the electrical conduction of Earth materials (in particular silicate minerals) must be considered. This is because: (1) fluorine may be stored in appreciable amounts of a few hundred to several thousand ppm in many minerals in the deep mantle such as olivine, garnet, pyroxenes, wadsleyite and ringwoodite [36][37][38], (2) fluorine-abundant phases such as phlogopite could be regionally enriched in the deep crust and upper mantle, leading to very high electrical conductivity in regional areas [17,20], and (3) the sensitivity of conductivity to fluorine may be comparable to H in nominally anhydrous minerals [17], and at higher temperature, the effect of fluorine on enhancing the conductivity of the host minerals exceeds that of H (protons) and thus dominates bulk conductivity, due to the much larger activation enthalpy of fluorine conduction (e.g., 130-220 kJ/mol) relative to proton conduction,~70-90 kJ/mol [2][3][4][5][6][7][8][9][10][11][12][13] (Figure 5). This would shed fundamental insight into the electrical structure of the deep Earth, although further experimental studies on other minerals are necessary.…”
Section: Fluorine Conduction and Implicationsmentioning
confidence: 99%